Effect of Organizational Excellence on Factors of Organizational Performance in Dubai Freezones - Aldarmaki, Sharifa; Yaakub, Kamarul Bahari; Adnan, Ahmad Amri Zainal (European Journal of Multidisciplinary Studies, 2023)
The importance of organizational excellence cannot be overemphasized because it allows the organization to improve its overall performance. This means organizational excellence can help any time of organization improve their performance, but only when dimensions of organizational excellence are well linked with factors of organizational performance. Therefore, the overall objective of this paper is to assess the effect of organizational excellence on factors of organizational performance in Dubai Freezones. An online questionnaire was completed by 201 respondents from Dubai Freezones which focused on determining the effects of organizational excellence on the internal and external factors of organizational performance. The data analyzed using descriptive and inferential statistics revealed unexpected findings. The findings reveal that organizational excellence does not have positive effect on the internal factors of organizational performance such as people and key factors. Further finding show that organizational excellence has positive effect on external factors of organizational performance which are customer and society factors. While these results show that dimensions of organizational excellence have potential to positively effect organizational performance, they also indicate that it is yet to have positive effect on certain factors of organizational performance in Dubai Freezones. The implication of these findings is that further investigation may be required to determine what variable may moderate the relationship between organizational excellence and all factors of organizational performance in Dubai Freezones in order to provide recommendations for other freezones in the UAE.
Keywords: Organizational Excellence, Organizational Performance, Internal Factors, External Factors, Freezones, Dubai.